From submission to dependence: Women’s status in a pelion village - Handman, Marie-Elisabeth (The Greek Review of Social Research, 1981)
Pouri is a Pelion village which long remained remote. Established in the middleof the 18th century, its history is that discontinuous one of those villages which receive successive migratory waves.The changes it has undergone (transition from share-croping or factory wage earning systems to agricultural self-employment; mechanization of certain farm-work) have always taken place at the expense of women. Their inferior position has not allowed them to benefit immediately from the economic and technical improvements; on the contrary, they pay the cost of it. either in extra work (1920-1955), or in increas ed isolation ( 1960-1970).’or to-day in a discrepancy between their aspirations (to live like urban housewives) and their village life characterized by boredom and disillusionment. For, if mechanization liberated them from what they call «slavery», i.e. an almost unbearable load of work, it did not give them the means of becoming autonomous and self-reliant. Moreover, they do not wish to become independent: they have interiorized their dependence so much that they consider it as a natural necessity.